The silk characteristics of jedung silkworm (Attacus atlas L.) reared on senggugu (Clerodendron serratum Spreng) food plant - MUHAMMAD INDRAWAN (Biodiversitas Journal of Biological Diversity, 2007)
The objective of this research was to determine the silk characteristics of Jedung silkworm reared on Senggugu food plant. Cocoon characteristics examined was the weight of cocoon and the value of Shell Ratio (SR). Meanwhile, the characteristics of fiber conclude the tensile strength, the elongation and the moisture absorption. The results showed that the range of cocoon weight was between 5.849 + 0.378 g. If it is compared to other cocoon reared on other food plants, the cocoons from Jedung silkworm were less weight. This wasprobably because of the characteristics of Senggugu leaf that was thinner and less water content which will produced cocoon with less weight. The lower weight of cocoon could affect to the value of measured SR. The value of SR was 9.828 + 1.475 %. The good range of SR value is between 19-20 %. The tensile strength was 14,444 + 5.270 g per denier. The good range of tensile strength is between 2.6 to 4.8 g per denier. The elongation was 2.184 + 2.168 %. This study showed the elongation was lower compared to other characteristics ofgood fiber with value more than 18 %. The moisture absorption varies between 20.214 + 0.618 %. It will cause fabric made from this material were considered cooler to wear, so that relatively good from the side of convenience.In general, characteristics of the fiber were relatively good. Therefore, it needs higher effort to increase weight of cocoon and the elongation of fiber.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: characteristics of fiber, Jedung silkworm, Senggugu food plant